2012
DOI: 10.1016/j.pocean.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale eddies in the Gulf of Aden and their impact on the spreading of Red Sea Outflow Water

Abstract: The Gulf of Aden (GOA) in the northwestern Indian Ocean is the receiving basin for Red Sea Outflow Water (RSOW), one of the World's few high-salinity dense overflows, but relatively little is known about spreading pathways and transformation of RSOW through the gulf. Here we combine historical data, satellite altimetry, new synoptic hydrographic surveys and the first in situ direct observations of subsurface currents in the GOA to identify the most important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 62 publications
8
56
0
Order By: Relevance
“…This water was contained in the large cyclone which lay around 47 • E, 12 • 30 N at day 40 of the mission. This confirms the conclusion drawn by Bower and Furey (2011) that westward drifting eddies can transport ICW into the Gulf of Aden and mix it with RSOW there.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…This water was contained in the large cyclone which lay around 47 • E, 12 • 30 N at day 40 of the mission. This confirms the conclusion drawn by Bower and Furey (2011) that westward drifting eddies can transport ICW into the Gulf of Aden and mix it with RSOW there.…”
Section: Methodssupporting
confidence: 90%
“…Indeed, gyres in the Gulf of Aden have a noticeable barotropic component (Bower et al, 2002;Bower and Furey, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most energetic currents are observed around C1, A2 and along the coastal "belt". In Bower and Furey (2012), Carton et al (2012) andL'Hégaret et al (2013), correlations are found between the surface circulation induced by the eddies and the structure of the salty outflows from the Red Sea and the Persian Gulf. The velocity map gives a first glimpse of the pathway of the PGW: in the western Sea of Oman, the water mass equilibrated and flowed along the southern coast; then, it was ejected northward from the coast at Ra's Al Hamra, under the influence of A1.…”
Section: Structure Of Mesoscale Eddies and Their Relation To The Pgw mentioning
confidence: 99%
“…These eddies are known to dominate the near-surface circulation offshore (see Fischer et al, 2002) and to induce horizontal transports. They have a vertical influence on the water masses at depth (see Furey, 2012, andCarton et al, 2012). Other processes can lead to the formation of such eddies, depending on the location and the season.…”
Section: Introductionmentioning
confidence: 99%